Pengembangan Materi Ajar Teks Fabel Kelas VII Berbasis Aplikasi Flipaclip - Dewi Meizar Mustika (Universitas Palangka Raya, 2023)
This research was conducted to (1) develop flipaclip application-based teaching materials so as to produce class VII fable text teaching material products in the form of learning videos, (2) describe the feasibility of class VII flipaclip application-based fable text teaching materials. This study used the Research and Development (R&D) method based on the Borg and Garl model modified by Sugiyono with 6 research stages namely potential and problem analysis, data collection, product design, design validation, design revision, and product testing. The results of this study are class VII fable text teaching material products based on the flipaclip application with an average score of 80% from material experts in the very good category, 82.89% from media experts in the very good category, 92.3% from subject matter teachers study Indonesian with very good category. So it can be concluded that the fable text teaching material product based on the flipaclip application in class VII SMP Negeri 1 Bangko Pusako is suitable for use in the learning process in schools, especially class VII.